Effect of adsorbed moisture on the pore size distribution of marine-continental transitional shales: Insights from lithofacies differences and clay swelling - Li, Pei; Zhang, J.; Rezaee, Reza; Dang, W.; Tang, X.; Nie, H.; Chen, S. (ELSEVIER, 2021)
The variation in pore water distribution within gas shale reservoirs has a significant effect on gas content, and thus on resource evaluation. However, the characteristics of water micro-distribution and its effects on pore parameters are still not well understood due to the mixed wettability of shale and the complexity of the pore structure. In this study, six lower Permian transitional shale samples from the southern North China Basin, humidified at four levels up to a relative humidity of 98%, were selected for moisture-equilibrated experiments and low-pressure N2 gas adsorption measurements. The results indicate that the adsorbed moisture in transitional clay-rich shales can be divided into capillary condensation water in the micropores and monolayer–multilayer adsorbed water in the non-micropores. Moreover, thermal maturity (VRo), total organic carbon, clay, and carbonate are positively correlated with the adsorbed moisture and micro-/mesopores, indicating that water in shales could be hosted in inorganic pores as well as in organic pores. Furthermore, the distribution of adsorbed moisture is mainly controlled by the VRo, component wettability (i.e., organic matter, clay, pyrite, and carbonate), and pore structure (micro-/mesopore distribution). In addition, a subtle adsorbed moisture may significantly reduce both the pore volume (PV) and specific surface area (SSA) of micropores, and the effect on micropores and SSA is more pronounced than that on the respective non-micropores and PVs. Additionally, the mechanism of clay swelling and pore expansion in clayey shale can provide certain insights for water–methane competitive adsorption, identifying clay type and pore size, and the formation of organo-mineral complexes.